2018
DOI: 10.1042/bst20170469
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA in cystic fibrosis

Abstract: Non-coding RNAs (ncRNAs) are an abundant class of RNAs that include small ncRNAs, long non-coding RNAs (lncRNA) and pseudogenes. The human ncRNA atlas includes thousands of these specialised RNA molecules that are further subcategorised based on their size or function. Two of the more well-known and widely studied ncRNA species are microRNAs (miRNAs) and lncRNAs. These are regulatory RNAs and their altered expression has been implicated in the pathogenesis of a variety of human diseases. Failure to express a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 91 publications
2
21
0
1
Order By: Relevance
“…miR-221 is increased in CF bronchial brushings, whilst its target, activating transcription factor 6 (ATF6; a transcription factor involved in the UPR), is decreased [138]. The role of dysregulated miRNAs in CF and other lung diseases has been more extensively reviewed elsewhere, for example Glasgow et al [139] and Dutta et al [140].…”
Section: Mirnas In Cfmentioning
confidence: 99%
“…miR-221 is increased in CF bronchial brushings, whilst its target, activating transcription factor 6 (ATF6; a transcription factor involved in the UPR), is decreased [138]. The role of dysregulated miRNAs in CF and other lung diseases has been more extensively reviewed elsewhere, for example Glasgow et al [139] and Dutta et al [140].…”
Section: Mirnas In Cfmentioning
confidence: 99%
“… 1 ncRNAs can be classified by length (small, 18–200 nt; long, >200 nt) or by function (housekeeping ncRNAs and regulatory ncRNAs), with research over the last two decades largely focusing on regulatory ncRNAs. 2 miRNAs, which are ∼22 nt long, are the most widely studied class of regulatory ncRNAs, and these molecules mediate post-transcriptional gene silencing in animals by controlling the translation of mRNAs into proteins. 3 lncRNAs, longer than 200 nt, are another subtype of regulatory ncRNAs that have a broad repertoire of functions in chromatin modification as well as in transcriptional, post-transcriptional, and translational regulation.…”
Section: Main Textmentioning
confidence: 99%
“… 3 lncRNAs, longer than 200 nt, are another subtype of regulatory ncRNAs that have a broad repertoire of functions in chromatin modification as well as in transcriptional, post-transcriptional, and translational regulation. 2 , 3 …”
Section: Main Textmentioning
confidence: 99%
“…We, and others, have previously shown that numerous miRNAs are differentially expressed in the lungs of CF adults 14,22,23 . The aim of this study was to investigate whether plasma microRNA expression profiles differ between the sexes in children with CF.…”
Section: Discussionmentioning
confidence: 76%
“…Many miRNAs have been shown to be dysregulated in the CF lung environment, including those with targets such as CFTR, IL-8, Target of Myb1 (TOM1) and activating transcription factor 6 (ATF6), as reviewed by Glasgow et al 14 . In this work, we sought to explore the circulating miRNA profile of paediatric CF plasma.…”
mentioning
confidence: 99%